Molluskicidal nanoemulsion of Neomitranthes obscura (DC.) N. Silveira for schistosomiasis control - Rangel, Leonardo da Silva; Paiva Machado, Francisco; Amaral, Raquel; Cláudia Rodrigues Da Silva, Ana; Santos, Marcelo Guerra; Albuquerque Dos Santos, José Augusto; Lidmar Von Ranke, Natalia; Rodrigues, Carlos Rangel; Rocha, Leandro; Faria, Robson Xavier (Frontiers in Pharmacology, 2023)
Schistosomiasis is caused by the parasite Schistosoma mansoni, which uses mollusks of the Biomphalaria genus as intermediate hosts. In 2020, approximately 241 million people worldwide underwent treatment for schistosomiasis. For this reason, the World Health Organization encourages research on alternative molluskicides based on plant species. The objective of this work was to investigate Neomitranthes obscura essential oil from leaf chemical composition and its essential oil nanoemulsion activity on intermediate hosts of schistosomiasis Biomphalaria glabrata control. The major chemical components of the Neomitranthes obscura essential oil were zonarene, seline-3,7(11)-diene, β-selinene, and α-selinene. The nanoemulsion tested using 24-well plate methodology showed lethality and juvenile mollusks with LC90 values of 53.9 and 25.0 ppm after 48 h, respectively, and on their spawning with an LC90 of 66.2 ppm after 48 h. Additionally, the nanoemulsion exhibited an LC90 value against the infective form of the parasite Schistosoma mansoni of 11.5 ppm after 4 h. This pharmaceutical formulation acted inhibiting the acetylcholinesterase activity and was not toxic for Mellanoides sp. This result suggests the use of this nanoformulation as a promising alternative in the control of Biomphalaria glabrata and the transmission of schistosomiasis.